Evaluation of Hearing Aid Manufacturers' Software-Derived Fittings to DSL v5.0 Pediatric Targets. - Folkeard, Paula; Bagatto, Marlene; Scollie, Susan (Journal of the American Academy of Audiology, 2020)
Background Hearing aid prescriptive methods are a commonly recommended component of evidence-based preferred practice guidelines and are often implemented in the hearing aid programming software. Previous studies evaluating hearing aid manufacturers' software-derived fittings to prescriptions have shown significant deviations from targets. However, few such studies examined the accuracy of software- derived fittings for the Desired Sensation Level (DSL) v5.0 prescription. Purpose The purpose of this study was to evaluate the accuracy of software-derived fittings to the DSLv5.0 prescription, across a range of hearing aid brands, audiograms, and test levels. Research Design This study is a prospective chart review with simulated cases. Data Collection and Analysis A set of software-derived fittings were created for a six- month-old test case, across audiograms ranging from mild to profound. The aided output from each fitting was verified in the test box at 55-, 65-, 75-, and 90-dB SPL, and compared with DSL v5.0 child targets. The deviations from target across frequencies 250-6000 Hz were calculated, together with the root-mean-square error (RMSE) from target. The aided Speech Intelligibility Index (SII) values generated for the speech passages at 55- and 65-dB SPL were compared with published norms. Study Sample Thirteen behind-the-ear style hearing aids from eight manufacturers were tested. Results The amount of deviation per frequency was dependent on the test level and degree of hearing loss. Most software-derived fittings for mild-to-moderately severe hearing losses fell within ± 5 dB of the target for most frequencies. RMSE results revealed more than 84% of those hearing aid fittings for the mild-to-moderate hearing losses were within 5 dB at all test levels. Fittings for severe to profound hearing losses had the greatest deviation from target and RMSE. Aided SII values for the mild-to-moderate audiograms fell within the normative range for DSL pediatric fittings, although they fell within the lower portion of the distribution. For more severe losses, SII values for some hearing aids fell below the normative range. Conclusions In this study, use of the software-derived manufacturers' fittings based on the DSL v5.0 pediatric targets set most hearing aids within a clinically acceptable range around the prescribed target, particularly for mild-to-moderate hearing losses. However, it is likely that clinician adjustment based on verification of hearing aid output would be required to optimize the fit to target, maximize aided SII, and ensure appropriate audibility across all degrees of hearing loss.